2020
DOI: 10.1101/2020.02.04.934182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bidirectional synaptic plasticity rapidly modifies hippocampal representations

Abstract: 15According to standard models of synaptic plasticity, correlated activity between 16 connected neurons drives changes in synaptic strengths to store associative 17 memories. Here we tested this hypothesis in vivo by manipulating the activity of 18 hippocampal place cells and measuring the resulting changes in spatial selectivity. 19 We found that the spatial tuning of place cells was rapidly reshaped via 20 bidirectional synaptic plasticity. To account for the magnitude and direction of 21 plasticity, we eval… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(82 citation statements)
references
References 108 publications
(463 reference statements)
9
73
0
Order By: Relevance
“…These protocols have shown both an increase and a decrease in synaptic efficacies occurring in synapses that were active seconds before or after the plateau potentials. This plasticity, coined "behavioral time synaptic plasticity" (BTSP), is therefore also likely to depend on synaptic eligibility traces, both for LTP and LTD. A recent paper has shown that these traces likely depend only on presynaptic activity and the existing synaptic efficacy, and that change in synaptic efficacies depends on the overlap between these traces and an instructive signal that is activated by the plateau potential [18]. The data therefore supports a two-factor model in which the two factors are presynaptic activity and an instructive signal.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…These protocols have shown both an increase and a decrease in synaptic efficacies occurring in synapses that were active seconds before or after the plateau potentials. This plasticity, coined "behavioral time synaptic plasticity" (BTSP), is therefore also likely to depend on synaptic eligibility traces, both for LTP and LTD. A recent paper has shown that these traces likely depend only on presynaptic activity and the existing synaptic efficacy, and that change in synaptic efficacies depends on the overlap between these traces and an instructive signal that is activated by the plateau potential [18]. The data therefore supports a two-factor model in which the two factors are presynaptic activity and an instructive signal.…”
Section: Introductionsupporting
confidence: 62%
“…Experimental results in CA1 using both in vivo and slice preparations strongly suggest that presynaptic activity generates synaptic eligibility traces for both LTP and LTD [17,19]. Prior modeling work [18] shows, using simulations, that these two opposing traces, combined with a weight dependence can account for the place field plasticity observed in vivo.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations